Nitrosative stress parameters as potential biomarkers in combat trauma - R. V. Fafula; Z. Y. Fedorovych; M. Z. Vorobets; O. K. Onufrovych; G. V. Galyk; M. Y. Kushynska; Z. D. Vorobets; O. M. Chemerys (Regulatory Mechanisms in Biosystems, 2025)
As a result of severe injuries and post-traumatic stress disorder, sexual dysfunction and fertility disorders are among the complications men experience. The mechanisms of the effects of combat trauma are complex and include an imbalance of the immune system, which leads to severe inflammatory reactions and other immunomodifying effects after injury. An early r e sponse to an acute inflammatory injury, such as wound healing, is the production of nitric oxide (NO) as a result of L-arginine metabolism. NO is an important regulator of cellular functions throughout the wound healing process, stimulating fibroblasts to produce collagen, promoting matrix deposition, remodeling, and angiogenesis. However, insufficient or excessive NO synthesis negatively affects wound healing. The aim of the study was to investigate the prognostic power of arginase activity parameters and individual NO synthase isoforms as potential biomarkers of nitrosative stress in men with combat trauma. The study e x amined 68 men with combat trauma, including 42 men aged 20 – 39 years and 26 men aged 40 – 53 years. Criteria for inclusion in the control groups: 30 healthy men aged 20 – 39 years and 18 men aged 40 – 53 years with normal levels of cNOs, iNOs and arg i nase activity, somatically healthy, without sexual dysfunction. In all groups, the activity of NO synthases and arginase as markers of nitrosative stress was measured spectrophotometrically in blood serum and lymphocyte samples. The prognostic power of the parameters of cNOS, iNOS and arginase activity in the combat trauma and control groups was determined by the receiver opera t ing characteristic curve (ROC curve). Based on the ROC analysis, the threshold value of cNOS activity in blood lymphocytes was determined, which is an integral highly sensitive criterion for unfavorable prognosis in combat trauma. For men aged 20 – 39 years, this figure is ≤37.5 nmol NADPH(H + )/min. mg with a sensitivity of 61.9% and a maximum specificity of 100 . 0 %, while for the group of men aged 40 – 53 years, the cutoff value is ≤38.4 nmol NADPH(H + )/min. mg with a sensitivity of 65. 4 % and a maximum specificity. In the ROC analysis of iNOS activity in lymphocytes of men with combat trauma in relation to healthy men, an excellent model quality was obtained with the maximum area under the ROC curve for patients of both age groups. The lymphocyte arginase activity in the two age groups of men with combat trauma were characterized by the very good diagnostic accuracy of the test. Thus, the parameters of oxidative-nitrosative stress, in particular the activity of constitutive and inducible isoforms of NO synthase and arginase in blood serum and lymphocytes can be potential markers in distinguishing pathological changes in men affected by combat (bullet and shrapnel wounds). The inducible isoform of NO synthase has been shown in studies to be a highly sensitive and highly specific marker regardless of the age of men.